Case Report: Mediastinitis Secondary to Deep Neck Abscess, Should Sternotomy be Done? - Noor, Muhammad Farhan; Lekatompessy, Michael; Dandanah, Maulidia Ayudika (Writing Center IMERI FMUI, 2023)
A deep neck abscess is a treatable infection in the deep cervical space. The condition may have life-threatening complications. A complication that can happen secondary to the abscess is mediastinitis, and treating a patient with such a complication could be challenging. To emphasize that treatment by exploration of the abscess and insertion of a mediastinal drain could be an alternative therapy compared to sternotomy for mediastinitis secondary to deep neck abscess. A 39-year-old male came to the ER with a chief complaint of swollen and neck tenderness for the past five days, along with difficulty swallowing and chest pain. Radiographic examinations showed a retropharyngeal abscess with a widening mediastinum. The patient underwent surgery to drain the abscess. Cervical and mediastinal drains were inserted, and the patient was transported to the Intensive Care Unit for observation. The patient was extubated after three days, and both drains were removed on the fifth day. Deep neck abscess is still common in Indonesia, and mediastinitis is a complication of deep neck infections. A surgical approach is necessary when mediastinitis occurs as it is considered a medical emergency. Not all ICU units in Indonesia can provide or manage open sternotomy patients. Identifying complications, early detection, and treatment is crucial in determining the patient’s prognosis.